2019
DOI: 10.1039/c9fo02020a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of betalains on atherogenic risk factors in patients with atherosclerotic cardiovascular disease

Abstract: After consumption of betalain-rich supplements of red beetroot and betacyanins-rich supplements of Opuntia stricta, the betanin appears in urine and plasma to improve the lipid profile, blood pressure, homocysteine and glucose levels of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 43 publications
1
28
1
Order By: Relevance
“…Further studies are required to determine betanin and indicaxanthin absorption in prickly pear varieties from the Canary Islands (Spain). This is of importance because betalains may affect age-related diseases because of their influence on human cell lifespan and aspects of age-dependent atherosclerosis [36,37]. Furthermore, no metabolites or degraded products could be detected by HPLC during the stages of the in vitro gastrointestinal digestion in the present study.…”
Section: Bioaccessibility In Pulps (Edible Fraction)mentioning
confidence: 58%
“…Further studies are required to determine betanin and indicaxanthin absorption in prickly pear varieties from the Canary Islands (Spain). This is of importance because betalains may affect age-related diseases because of their influence on human cell lifespan and aspects of age-dependent atherosclerosis [36,37]. Furthermore, no metabolites or degraded products could be detected by HPLC during the stages of the in vitro gastrointestinal digestion in the present study.…”
Section: Bioaccessibility In Pulps (Edible Fraction)mentioning
confidence: 58%
“…In the most recent crossover RCT conducted on non-smoking men (n = 48, aged 45-55, BMI: 25-35 kg m −1 ) with coronary artery disease (CAD), participants who were given daily capsules of betacyanin-rich extract (containing 50 mg of total betacyanin) of cactus pear for two weeks showed significant reduction in SBP of 3.16 mmHg. 43 Contradictory findings were reported in the other three RCTs. 16,42,44 Grube et al found no changes in SBP and DBP when overweight and obese individuals (n = 123, 30 male and 93 female, aged 33-57) consumed 3 g day −1 of litramine tablets (fibre complex from cactus pear) or placebo for a total of 56 days.…”
Section: Human Studiesmentioning
confidence: 67%
“…Effects of cacti on blood pressure (BP) in human studies. In terms of clinical evidence, a total of five human studies 16,32,[42][43][44] explored changes in BP but only two 32,43 reported significant improvements. The first study is a pilot study with no placebo group to compare against the treatment group.…”
Section: Human Studiesmentioning
confidence: 99%
“…In another study, betanin was not detected in plasma at any time point post-ingestion of 250 mL of beetroot juice or 300 g of whole beetroot, containing near 194 and 66 mg of betanin respectively [ 177 ]. Minimal amounts of betanin in plasma (< 1 µg), 3, 8, and 24 h after supplementing male patients with extracts containing 16 and 35 mg of betanin and after 2 weeks of supplementation (<3 µg) have been reported [ 178 ]. Regular consumption for long periods (between 1 and 6 weeks) of beetroot products seems to be the solution to overcome low betanin levels in biological fluids by promoting stabilization of the systemic levels, where betanin and their deglucosylated, decarboxylated and dehydrogenated metabolites are consistently described [ 24 ].…”
Section: Bioactive Compounds In Beetroot Product Interventionsmentioning
confidence: 99%